تطور معدل الفائدة في الفكر الأقتصادي - بنابي, فتيحة (Université de M'sila, 2017)
The interests rates is one of the most important indicator in the Capitalist Economy thought, because of its impact on macroeconomic and microeconomic variables. Whereas the economic think differ on the positive or negative origin of this impact. This matter lead us to address through this research views of some old civilizations and old religions too, and also the views of the economic thought through its various schools namely: the business school, the school of marginal trade, the classical school, the Keynesian school and the Neo-Keynesian school too. Adding the rational expectations theory and the contemporary theory, where some of them promotes the low level interests rates due to increase of the investment, employment and production, whereas others promotes its high level. This difference is due for different reasons as: the increase of savings, and the necessity to pay a fair price on the borrowed capital, adding to this more effects and other reasons we will discuss throughout this research.
Keywords: interest rate, interest rate, economic thought, economic theories.